THE IMPLICATIONS OF THE PRO-ENVIRONMENT MOVEMENT ON THE EMOTIONAL MANAGEMENT OF STUDENTS AT THE UPT JATIAN OF THE ANNUQAYAH LUBANGSA ISLAMIC BOARDING SCHOOL - Qismatun Ni'mah; Toat Haryanto (Living Sufism: Journal of Sufism and Psychotherapy, 2024)
This study seeks to elucidate two facets. Firstly, the presence of the pro-environment movement at the UPT Jatian Waste Laboratory of Pondok Pesantren Annuqayah Lubangsa. Secondly, the ramifications of the pro-environment movement at the UPT Jatian Waste Laboratory on the emotional regulation of santri at Pondok Pesantren Annuqayah Lubangsa. This study aims to ascertain the influence of the pro-environment movement on the emotional regulation of santri. To achieve this objective, the researcher employs a case study methodology, integrating two theoretical frameworks: Pro-Environmental Behaviour Theory, which emphasizes actions directed towards environmental conservation, and Emotional Intelligence Theory, which assesses the effects of the pro-environment movement. The study finds that the pro-environment movement serves as an alternative for establishing environmentally conscious pesantren and aims to enhance santri consciousness regarding the significance of environmental stewardship. Numerous procedures in environmental conservation encompass Reduction, Reuse, and Recycling. As a result, santri recognizes the need for environmental preservation. The execution of this maneuver entails many facilitating and obstructive elements. Detrimental factors encompass opposition from santri who have not embraced the pro-environment movement, whereas beneficial factors consist of santri who have accepted it and possess the ability to regulate their emotions, thereby enhancing their creativity and eagerness to engage in pro-environment initiatives.